The Performance of Postmenopausal Women in the Prevention of Osteoporosis Based on Health Belief Model - Seyyed Mansour Kashfi; Ali Khani Jeihooni; Hasan Jamshidi; Mina Bahmandoost (Guilan University of Medical Sciences, 2019)
Introduction: Osteoporosis is one of the most important causes of illness and disability in postmenopausal females, characterized by a decrease in bone mass and increased fracture probability. Determination of the factors influencing the adoption of preventive behaviors for osteoporosis in postmenopausal females is necessary by using patterns such as the health belief model that identifies and reinforces the factors affecting the behaviors. Objective: The current study aimed at determining the performance of postmenopausal females living in Fasa City, Iran in preventing osteoporosis based on the Health Belief Model. Materials and Methods: The current cross-sectional study was conducted on 380 females aged >50 years covered by Fasa health centers. They were selected by simple random sampling method. The data gathering tool was a questionnaire that its validity and reliability have already been confirmed. It included demographic information, knowledge assessment, health belief model scale constructs (susceptibility, severity, benefits, barriers, motivation, perceived self-efficacy, and guide to action), as well as nutritional and walking status questionnaires to prevent osteoporosis in females. Finally, the data were analyzed through descriptive indices (Mean, SD) and analytical statistic tests, including the Pearson correlation coefficient, and multiple linear regression analysis. Results: The Mean age of the subjects was 58.25±6.59 years and their average Body Mass Index (BMI) was 22.25±3.01 kg/m2. These variables predicted 31.5% and 28.4% of the walking and nutritional behavior variances of osteoporosis prevention, respectively. Meanwhile, among the health belief model constructs, perceived susceptibility constructs predicted both nutritional (P=0.001) and walking behaviors (P=0.02). Conclusion: Based on the results of this study and considering the predicting power of the health belief model, especially the perceived susceptibility construct, and the vulnerability of the females, it is recommended to implement accurate educational programs based on the health belief model rather than using traditional methods of education to raise their perceived susceptibility to osteoporosis, as well as increasing self-efficacy and perceived benefits.